5G: performance and evaluation of FS‐FBMC against OFDM for high data rate applications at 60 GHz. Issue 5 (1st July 2018) - Gomes, Rodolfo; Reis, Joao; Al‐Daher, Zaid; Hammoudeh, Akram; Caldeirinha, Rafael F.S.
Abstract : This study presents a frequency spreading filter bank multi‐carrier (FS‐FBMC) waveform as a potential candidate for the fifth generation (5G) network applications at millimetre‐waves (mmWaves). The proposed model is developed based on the orthogonal frequency division multiplexing (OFDM) waveform standardised by IEEE 802.15.3c for 60 GHz high data‐rate applications. The effects of non‐linearities of power amplifiers (PAs) at 60 GHz for both OFDM and FS‐FBMC are presented and compared using a realistic PA model. In particular, the sensitivity of both transmission schemes to the non‐linear effects is investigated and its impact on the performance degradation in terms of output‐power‐backoff, is characterised over typical indoor line‐of‐sight, kiosk and residential, 60 GHz IEEE channel models. The assessment metrics considered are bit error rate and out‐of‐band emissions. This study concludes radio access schemes for future communication generations, i.e. 5G may employ OFDM for up‐link and FS‐FBMC for down‐link due to the sensitivity to PA non‐linearities of both waveforms.